Tiny Noticeable Things - Webster, Adrian (Ascent Audio, 2021)
Discover how you can draw people in and achieve greater success, in just a few minutes each day TNTs are Tiny Noticeable Things. They are all the little things that people don't need to do, but do. Though small, they create the biggest, longest lasting impressions in people's minds; they show how much you care; they make and break relationships-yet they cost nothing. In Tiny Noticeable Things: The Secret Weapon to Making a Difference in Business, you'll learn how to use the explosive power of TNTs to get where you want to be in business and in everything you do. If you feel that you are just on the verge of ascending to the next level but aren't quite certain how to make the final push, this book is for you. Adrian Webster is a bestselling business author and motivational speaker and in his latest book, he not only shares his own insights, but invites over 100 people to share their experiences of the differences TNTs have made. You'll discover how far you can get with gestures as small as remembering a person's first name or sending a handwritten note. The effect these little engagers can have is quite phenomenal. Listen to Tiny Noticeable Things to learn how and why to take those extra-mile steps to penetrate straight through the conscious mind and gain fast-track access to the results you're after.